Hubungan Pengetahuan Dengan Peran Kader Posyandu Dalam Upaya Pencegahan Penyakit Tidak Menular Di Puskesmas Bukit Hindu - Tenun, Tenun; Carolina, Putria; Rosela, Kristin (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Non-communicable diseases (NCDs) are a group of diseases that are not caused by infection, are chronic, and usually develop slowly over time. The increasing burden of non-communicable diseases (NCDs) is caused by various preventable risk factors, including smoking habits, unhealthy diets, lack of physical activity, and alcohol consumption. Efforts to resolve the problem of non-communicable diseases in the community require the important role of active community involvement, especially Posyandu cadres. The government also issued a policy regarding Community-Based Health Efforts (UKBM) such as Posyandu which is expected to be able to resolve health problems in the community to detect and control non-communicable diseases (NCDs) early. This study was to determine the relationship between knowledge and the role of Posyandu cadres in efforts to prevent non-communicable diseases in the work area of the Bukit Hindu Community Health Center UPTD, Palangka Raya City. This research uses a cross-sectional method, namely research that. aims to study the dynamics of the correlation (relationship) between independent variables and dependent variables by means of an observation approach or data collection at one time ( point time approach ) with a sample of 50 respondents. The results of the study showed that there was a significant relationship between knowledge and the role of Posyandu cadres in efforts to prevent non-communicable diseases in the work area of the UPTD Bukit Hindu Health Center, Palangka Raya City. The implication of the research results is that there is a significant relationship between knowledge and the role of cadres, reinforcing that the quality of cadres is highly dependent on the extent to which they understand the tasks and functions in Posbindu PTM . Interventions in the form of regular training, provision of adequate measuring tools and strengthening motivation are very necessary so that cadres can carry out their roles optimally and sustainably.